2019
DOI: 10.1213/ane.0000000000003360
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Levorphanol, a G-Protein Biased Opioid Analgesic

Abstract: While levorphanol shares many of the same properties as the classic opioid morphine, it displays subtle differences that may prove helpful in its clinical use. Its G-protein signaling bias is consistent with its diminished respiratory depression, while its incomplete cross tolerance with morphine suggests it may prove valuable clinically with opioid rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Similar signaling profiles have been associated with nebivolol (Erickson et al, 2013), alprenolol , and propranolol (Azzi et al, 2003;Baker et al, 2003). The diminished respiratory depression potential of the opioid analgesic levorphanol (over morphine) has been attributed to its biased signaling profile (lack of b-arrestin2 recruitment) (Le Rouzic et al, 2019). In fact, the dependence liability of oxycodone, hydrocodone/paracetamol, and hydromorphone has been attributed to biased signaling (toward G protein vs. b-arrestin) (Johnson et al, 2017).…”
Section: B Assessing the Impact Of Biased Signaling From Known Ligandsmentioning
confidence: 70%
“…Similar signaling profiles have been associated with nebivolol (Erickson et al, 2013), alprenolol , and propranolol (Azzi et al, 2003;Baker et al, 2003). The diminished respiratory depression potential of the opioid analgesic levorphanol (over morphine) has been attributed to its biased signaling profile (lack of b-arrestin2 recruitment) (Le Rouzic et al, 2019). In fact, the dependence liability of oxycodone, hydrocodone/paracetamol, and hydromorphone has been attributed to biased signaling (toward G protein vs. b-arrestin) (Johnson et al, 2017).…”
Section: B Assessing the Impact Of Biased Signaling From Known Ligandsmentioning
confidence: 70%
“…Later experiments have found that the apparently biased agonists assumed to have high G protein efficacy, oliceridine, PZM21, and SR17018 actually exhibit low G protein efficacy relative to the prototypical MOR agonist morphine, a crucial parameter not reported in the earlier work (Burgueño et al, 2017; Hill et al, 2018; Yudin and Rohacs, 2019; Gillis et al, 2020). Similarly, buprenorphine and levorphanol, morphinans proposed as biased (Ehrlich et al, 2019;Le Rouzic et al, 2019;Pedersen et al, 2020), also have relatively low intrinsic efficacy for G protein activation (McPherson et al, 2010) as do a set of structurally distinct, putatively biased mitragynine-based compounds (Kruegel et al, 2016).…”
Section: Applicability To G Protein/arrestin Bias At a Prototypical Gpcrmentioning
confidence: 90%
“…Despite this, there was a good correlation observed between lower intrinsic efficacy and improved safety profile in a preclinical mouse model. Rodent experiments on oliceridine (DeWire et al, 2013), PZM21 (Manglik et al, 2016, but see Hill et al, 2018, SR17018 (Schmid et al, 2017), mitragynine (Váradi et al, 2016), and levorphanol (Le Rouzic et al, 2019) have suggested these compounds may have improved respiratory profiles over morphine. An alternative explanation to bias for these improvements may lie in the low intrinsic efficacy of these compounds, which is close to the uniquely low efficacy of buprenorphine, which may have an improved therapeutic window (Wolff et al, 2012).…”
Section: Relevance Of Efficacy and Biased Signaling To The Developmenmentioning
confidence: 99%
“…Recently, it was shown that the antinociceptive actions of levorphanol were mediated via G-protein biased MOPr agonism (Le . Furthermore, levorphanol produced significantly less respiratory depression than morphine at equal doses (Le Rouzic et al, 2019).…”
Section: Mixed Kopr/dopr/mopr Compoundsmentioning
confidence: 86%
“…Levorphanol is a full agonist at both MOPr and DOPr, and a partial KOPr agonist (Le Rouzic et al, 2019). Levorphanol was effective in treating chronic pain resulting from malignancies and bone or joint disease (Glazebrook, 1952), and post-operative pain following abdominal surgery (Morrison et al, 1971).…”
Section: Mixed Kopr/dopr/mopr Compoundsmentioning
confidence: 99%